From hydrated layered-spinel lithium manganate composite to high-performance spinel LiMn2O4: A novel synthesis tuned by the concentration of LiOH. Issue 15 (15th October 2017) - Jiang, Caihua; Tang, Zilong; Zhang, Zhongtai
Abstract: To obtain high-performance spinel LiMn2 O4, various types of hydrated layered-spinel lithium manganate composites have been controllably synthesized through the hydrothermal process. It is found that the composition and morphology of these intermediate products can be tuned by the concentration of LiOH: Li + act as the template and OH - provide the required alkaline environment. In particular, the nanostructure varies from nanowires to nanosheets at different levels, depending on the phase ratio of the spinel phase ranging from 0% to 100%. Phase purity and the corresponding electrochemical properties of the as-prepared LiMn2 O4 products are further tailored through the subsequent heat treatment. With the optimized LiOH concentration of 0.08 M, the resulting LiMn2 O4 cathode material exhibits the best electrochemical performance with the initial discharge capacity of 121.7 mA h g −1 at 1 C and 117.8 mA h g −1 at 30 C, while a retention over 90% can be achieved after 1500 cycles. This study will help deepen understanding of the function mechanisms and further direct the novel synthesis from hydrated layered-spinel lithium manganate composites to high-performance spinel LiMn2 O4 cathode materials.